Práticas de humanização desenvolvidas nos hospitais estaduais do Norte do Paraná : Acolhimento com classificação de risco em pronto socorro : avaliação de usuários e profissionais de saúde - Sardinha, Denise da Silva Scaneiro (2016)
Humanization is a key issue in public health policies and serves as the basis of several hospital care practices. Reception with Risk Evaluation and Classification brought significant changes to the work process of the nurses, allowing them to organize the waiting line and prioritize the emergency cases. This study aims to know and understand the perceptions of the care activities provided to users of the three state hospitals located in the city of Londrina, north of Paraná state, based by the proposals of the National Humanization Policy, in the Reception with Risk Evaluation and Classification, based on the opinions of nurses, nursing technicians and users of SUS. This is a descriptive study with qualitative approach, whose study population will consist of nurses and nursing technicians and users. Were included in this research: three nurses, three nursing technicians and six users of each institution, totaling 36 interviews. This analysis resulted in the development of four categories: Priority for those with life-threatening; Patient is well attended, but the professional is not identified; Someone to listen and Time to make a proper humanization. The research groups recognize the importance of the reception and risk classification as a method of prioritizing care for patients who have a risk of death or major damage. With this study, we show that the users recognize the improvement of their care in emergency rooms with the reception and risk classification, but disagree when they have to wait after the classification. Otherwise, in the reporting of nursing workers, remains clear that they were not satisfied, due to high demand of users in emergency rooms, the difficulty of accommodation and lack of physical structure resulting loss in quality of care and assistance to users. This study is expected to contribute with practices for managers and health workers and users to oversee and evaluate the actions that have been institutionalized and are being implemented and thus make the necessary.